Dietary of Spirulina Platensis through Feed Against Weight and Length Final, Hepatomatic Indek, and Visceral Organ Profile of Tilapia (Oreochromis Niloticus) and Pangasius Sp. - Cahyono Purbomartono; Ardhana Wikaneswari; Dini Siswani Mulia; Gayuh Prasetyo Budi (UM Purwokerto Press, 2023)
Consumer needs for tilapia and pangasius can be met with high stocking densities in cultivation intensification, large amounts of feed on limited land. Poor management of intensive aquaculture causes leftover feed and faeces to settle to the bottom of the pond, producing high levels of ammonia which inhibits growth. This study aims to increase growth, development of gonads and visceral organs with Spirulina platensis diet. The observation method is used in research with a complete random design, applying 3 treatments and 1 control with 4x replications. Observations included final length and weight, index of hepatosomatic (HSI), and index of visceral somatic (VSI). The results showed that the Spirulina platensis diet increased the final weight and length, HSI of tilapia and catfish significantly, but not significantly to VSI. This shows that the Spirulina platensis diet can be used to increase the growth and development of gonads.